1989
DOI: 10.3109/00365598909180819
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Prostatic Cancer in a Defined Population

Abstract: Health-service costs for prostatic adenocarcinoma were calculated on the basis of 101 patients resident in the Linköping area throughout their illness and who died in 1984-1985. At the time of diagnosis 54 tumours were advanced and 47 were localized. Primary treatment was expectant or surgical in 77 and oestrogen therapy in 17 cases. The average number of life-years lost was 4.3 in the total series and 10.7 in the men younger than 70. The median cost per case, SEK 50,000 (US dollars 7,900), was significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

1990
1990
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 3 publications
2
25
0
2
Order By: Relevance
“…Substitution of hospital admissions with ambulant visits would not significantly reduce the expenses because nearly two-thirds (62%) of the patients had at most two hospital admissions and were treated within the first year (66%) or second year (78%) of diagnosis. In accordance with three other Scandinavian studies (12)(13)(14), we found that the average consumption of health-service resources in many terms was concentrated (3 times higher) in the group of patients who finally died from prostate cancer. Our study is also in agreement with Otnes et al (12) and Aus et al (13) in terms of hospital care requirements measured as median admission time (28 days).…”
Section: Burden To the Health-care Systemsupporting
confidence: 92%
“…Substitution of hospital admissions with ambulant visits would not significantly reduce the expenses because nearly two-thirds (62%) of the patients had at most two hospital admissions and were treated within the first year (66%) or second year (78%) of diagnosis. In accordance with three other Scandinavian studies (12)(13)(14), we found that the average consumption of health-service resources in many terms was concentrated (3 times higher) in the group of patients who finally died from prostate cancer. Our study is also in agreement with Otnes et al (12) and Aus et al (13) in terms of hospital care requirements measured as median admission time (28 days).…”
Section: Burden To the Health-care Systemsupporting
confidence: 92%
“…6 He also noted that the survival time did not affect the total cost. This is felt to be secondary to the fact that most palliative, and expensive, procedures are required during that last year of life when local tumor growth or metastases require treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Uno dei primi tentativi di stima del costo diretto sanitario determinato dal CP è stato effettuato da Carlsson nel 1989 [17]. Carlsson calcolò il consumo di risorse sanitarie dalla diagnosi di CP fino al decesso in 101 pazienti deceduti tra il 1984 e il 1985 in Svezia (54% con carcinoma avanzato già alla diagnosi).…”
Section: Aspetti Economici Del Cancro Della Prostataunclassified
“…Nel semestre in cui si verifica la diagnosi i costi sanitari ammontano a circa 10-14.000 dollari [73,77] in relazione soprattutto ai ricoveri e pertanto al tipo di trattamento (combinazione di chirurgia e terapia medica vs singole strategie), ma anche alla comorbidità, al reddito e all'area geografica. Il periodo che precede strettamente il semestre in cui si verifica il decesso ha anch'esso una maggiore intensità di cure sanitarie, con un costo che si aggira sui 7-8.000 dollari/anno [77], mentre nel semestre terminale i costi variano da 11.000 dollari a 13.000 dollari, in ragione della causa di morte, della comorbidità e dello stadio iniziale della malattia [13,17,33,41,72,77,96]. Non ci sono, purtroppo, analisi economiche specifiche per lo scenario sanitario italiano attuale.…”
Section: Aspetti Economici Del Cancro Della Prostataunclassified